Warszawa – miasto, które nie istnieje - Czaja, Justyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
Warsaw - a city that does not exist The subject of the article is attempts in cinema and comics to reconstruct the image of pre-warWarsaw. The use of archival photographs of the capital, old postcards, and computer reconstructions using 3D technology increase the realism of the presentation, and provide the effect of intuition, intimacy, and directness. AWarsawnon-existent today comes to life again on the screen and in the pages of the comic book.